2017
DOI: 10.5513/jcea01/18.3.1937
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genotype on the behaviour of free range chickens

Abstract: The purpose of this experiment was to investigate the behaviour of fast-and slow growing chickens, when the birds had access to the outdoors. Fifty of both 1-day-old male chicks of a laying hybrid ISA BROWN (IB) and broilers ROSS 308 (RS) were kept in two pens in the same building. In each group ten birds were marked with a colored spray. From three weeks of age the birds had access to the outdoors. From the age of one to seven weeks old, one day a week the marked birds were observed from 8:00 to 18:00 every t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Lichovnikova et al., 2017 compared brown layer male chicks with male fast growing broiler chicks in the first 7 weeks of their live and found that the layer chicks were more active, whereas broiler chicks were sitting more.…”
Section: Assessmentmentioning
confidence: 99%
“…Lichovnikova et al., 2017 compared brown layer male chicks with male fast growing broiler chicks in the first 7 weeks of their live and found that the layer chicks were more active, whereas broiler chicks were sitting more.…”
Section: Assessmentmentioning
confidence: 99%
“…Given the welfare issues associated with rapid growth, there has been increasing interest in the potential of using slower growing broiler strains for commercial production. Although previous studies have evaluated the welfare or welfare-related outcomes of fast- and slower growing broilers (e.g., Bokkers and Koene, 2003 ; Fanatico et al, 2005 ; Lichovníková et al, 2017 ; Wilhelmsson et al, 2019 ; Dixon, 2020 ; Mancinelli et al, 2020 ; Weimer et al, 2020 ), many of these studies directly compared a limited number of strains (e.g., 1 conventional vs. 1 slower growing strain: Bokkers and Koene, 2003 ; Wallenbeck et al, 2016 ; Lichovníková et al, 2017 ; Wilhelmsson et al, 2019 ; Weimer et al, 2020 ), evaluated welfare in nonintensive settings (e.g., Fanatico et al, 2005 ; Mancinelli et al, 2020 ), and/or evaluated slower growing birds at comparably low body weights (e.g., <2 kg: Bokkers and Koene, 2003 ; Lichovníková et al, 2017 ). Additionally, even among strains considered to be slower growing, there is a large range in growth rates and no consensus about growth rate cut-offs that ensure or lead to improved welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Fanatico et al, 2005;Mancinelli et al, 2020), and/or evaluated slower-growing birds at comparably low body weights (e.g. < 2 kg: Bokkers and Koene, 2003;Lichovníková et al, 2017). Additionally, even among strains considered to be slower growing, there is a large range in growth rates and no consensus about growth rate cut-offs that ensure or lead to improved welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Bokkers and Koene, 2003;Fanatico et al, 2005;Lichovníková et al, 2017;Wilhelmsson et al, 2019;Dixon, 2020;Mancinelli et al, 2020;Weimer et al, 2020), many of these studies directly compared a limited number of strains (e.g. 1 conventional vs. 1 slower-growing strain: Bokkers and Koene, 2003;Wallenbeck et al, 2016;Lichovníková et al, 2017;Wilhelmsson et al, 2019;Weimer et al, 2020), evaluated welfare in non-intensive settings (e.g. Fanatico et al, 2005;Mancinelli et al, 2020), and/or evaluated slower-growing birds at comparably low body weights (e.g.…”
mentioning
confidence: 99%